Analysis of the Relationship between Responsiveness, Assurance, and Attention to Patient Family Satisfaction in the Sub-Acute Room of the Aceh Mental Hospital in 2021 - Desivaria Sandi; Zulfendri Zulfendri; Siti Khadijah (Budapest International Research and Critics University, 2022)
The purpose of this study is to analyze the relationship between responsiveness, assurance, and attention to patient family satisfaction in the Sub-Acute Room of the Aceh Mental Hospital in 2021. The type of research that will be used is a quantitative study. The research location chosen is the Aceh Mental Hospital, as the only public service institution for tertiary psychiatric services in the Aceh region. The population in this study are the families of patients who came to visit patients who were being hospitalized within 2x24 hours or more, and also the families of patients who came to pick up patients who had finished in sub-acute inpatient care after the day of treatment was completed at the hospital. The number of samples obtained is 59 people, so the researcher will take a sample of 60 patients' families within the planned one month research period as respondents to represent the existing population. This study was analyzed using the spearman correlation test. The results of the study show that there is a significant relationship between responsiveness with patient family satisfaction. There is a significant relationship between assurances with patient family satisfaction. There is a significant relationship between attentions with patient family satisfaction.